Comparative effectiveness of tele-monitoring of users with pacemakers at 6 months after implant: the nordland study - López Villegas, Antonio; Lappegard, Knut Tore; Catalán Matamoros, Daniel Jesús (2017)
Comunicación oral presentada en el 3er Congreso Internacional de Comunicación en Salud (3ICHC), celebrado los días 19 y 20 de octubre de 2017 en la Universidad Carlos III de Madrid. The main purpose of the present study was to assess the effectiveness of tele-monitoring (TM) in patients with pacemakers regarding reliability, safety and health-related quality of life, compared to traditional follow-up in outpatient clinic.